2015
DOI: 10.1039/c4en00192c
|View full text |Cite
|
Sign up to set email alerts
|

Potential exposure and treatment efficiency of nanoparticles in water supplies based on wastewater reclamation

Abstract: We present current knowledge on nanoparticle fate in wastewater reclamation systems for potable reuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Similarly for CeO 2 and Ag, particle concentrations of 0.1 ng/L and 1.9 ng/L, respectively, were calculated in tap water (Yang & Westerhoff 2014). Kirkegaard et al (2015) used a mass flow analysis to model ENM fate and treatment in two typical potable reuse systems for reclaimed wastewater (advanced membrane treatment and bank infiltration) and found that ENMs may be present in tap water in the ng/L to μg/L range under a worst‐case scenario. More research is needed to elucidate removal efficiencies of ENMs during various treatment stages and conditions, particularly as more robust detection methods become available and as ENM types and uses evolve.…”
Section: Behavior Of Enms In Dwtpsmentioning
confidence: 99%
“…Similarly for CeO 2 and Ag, particle concentrations of 0.1 ng/L and 1.9 ng/L, respectively, were calculated in tap water (Yang & Westerhoff 2014). Kirkegaard et al (2015) used a mass flow analysis to model ENM fate and treatment in two typical potable reuse systems for reclaimed wastewater (advanced membrane treatment and bank infiltration) and found that ENMs may be present in tap water in the ng/L to μg/L range under a worst‐case scenario. More research is needed to elucidate removal efficiencies of ENMs during various treatment stages and conditions, particularly as more robust detection methods become available and as ENM types and uses evolve.…”
Section: Behavior Of Enms In Dwtpsmentioning
confidence: 99%
“…Several methods such as phytoremediation, coagulation and flocculation, membrane filtration, and adsorption have been assessed to find suitable methods for removing metal-containing NPs from water and wastewater [20][21][22][23][24][25][26]. Because of the drawbacks of other methods including fouling in membrane filtration and high volume of sludge in coagulation and flocculation process, the adsorption process has been reported as the most efficient and economical method [27].…”
Section: Introductionmentioning
confidence: 99%
“…Another important property is dissolution potential, or the potential to release soluble metal species as free ions or metal complexes. The useful properties of metal‐based ENPs mean that they are widely produced and incorporated into consumer products and industrial applications , and they are consequently increasingly being released into human‐made and natural aquatic systems.…”
Section: Introductionmentioning
confidence: 99%